Humanistic Trend in Sociology and the Problem of Social Reality - Šerpytytė, Rita (Problemos, 1995)
The paper deals with the difficulties facing the humanistically oriented social theory in its attempt to found the possibility of the cognition of social reality as specific one. The theories of social knowledge by Wilhelm Dilthey and Alfred Schütz are analysed.